Bis[N, N′-bis(anilino)glioximato]platinum(II) complex: synthesis, characterization and biological activity. Issue 1 (17th January 2022) - Eroğlu Gülümsek, Özge; Erciyas Baykal, Esma; Küçükpolat, Cansu; Önal, Emel; Balcik-Ercin, Pelin; Yagci, Tamer; Ahsen, Vefa; Gürek, Ayşe Gül
Abstract: N, N ′-bis(aniline)glyoxime (H2 L, 1 ) has been prepared from aniline and ( E, E )-dichloroglyoxime (DCGO) or ( E, E )-dibromoglyoxime (DBGO). The reaction of N, N′ -bis(aniline)glyoxime (H2 L, 1 ) with solution of PtCl2 in dimethylsulfoxide produced brown-colored bis( E, E -dioximato)platinum(II) complex {[( E, E )-Pt(HL)2 ]} (1a ) featuring N -chelating ligand. The crystal structure of this complex has been identified by X-ray diffraction on a single-crystal. In vitro assay of proliferation, cell death, DNA-damage and cell uptake activities of 1 and 1a were tested in HCC cell lines, SNU-182 and HUH-7. 1a has an anti-proliferative effect in HCC cells, however, 1 did not. Furthermore, the cellular uptake of 1a was relatively high compared to cisplatin cellular platinum levels. Compatible with proliferation and cellular uptake results, treatment with 1a caused DNA-damage and subsequent apoptosis in both HCC cell lines. Abstract : UF0001